PENGGUNAAN GAWAI DALAM PEMBELAJARAN BAHASA INGGRIS BAGI ANAK BERKEBUTUHAN KHUSUS DI SMK NEGERI 8 SURAKARTA - Wardhani, Puspita Indra; Nisa, Shelviana Khoirun; Ratnakannyaka, Illiyyin Wasistha; Damayanti, Laksitha; Sari, Denisa Elvina (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Children with special needs (ABK) are individuals who have different characteristics from individuals physically, intellectually and emotionally. Children with special needs need special education and services to optimize their potential in learning activities. Gadgets as one of the learning media that have many advantages can help children with special needs in the learning process. The purpose of this study was to determine whether the media (gadgets) can create effective learning activities for students with special needs in the classroom. This study uses qualitative methods by observing learning activities for English subjects for 2 weeks. The results showed that the use of devices by students with special needs can make it easier for students to access subject matter and help to do assignments from the teacher.